Soft Upper‐Limb Wearable Robotic Devices: Technology and Applications - Bibhu Sharma; Phuoc Thien Phan; James Davies; Trung Thien Hoang; Chi Cong Nguyen; Adrienne Ji; Kefan Zhu; Emanuele Nicotra; Nigel H. Lovell; Thanh Nho Do (Advanced Intelligent Systems)
One of the practical applications in the field of soft robotics involves the development of soft robotic wearable devices. These devices make use of their intrinsically compliant structures to interact safely and harmoniously with the human body. While soft wearable robots demonstrate their utility in lower‐limb applications for locomotion, the upper‐limb domain offers significant prospects in a wide range of applications that soft robotic technology can address. In this review, the current state of technology in the field of soft wearable upper limbs is systematically analyzed and categorized. Categorizations are made based on their applications in rehabilitation, activities of daily living support, and human augmentation. Furthermore, in this study, also contemporary technological aspects, encompassing sensing technology and control systems, are explored. Despite exciting potential in this domain, several limitations from existing devices inherently impede widespread adoption and thus hinder further progress in the field. In this study, also an overview of the different facets of the domain is provided and key considerations for the advancement of soft wearable robotic devices intended for upper‐limb applications are prescribed.